Mainstreaming biodiversity and nature’s contributions to people in Europe and Central Asia: insights from IPBES to inform the CBD post-2020 agenda - Sandström, Camilla (2023)
Recent global and regional assessments of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) show that Nature’s Contributions to People (NCP) are under an alarming threat due to the continuing loss of biodiversity. These assessments call for increasing conservation efforts and a more sustainable use of biodiversity to enhance the chances of halting biodiversity loss and reversing current trends. One of the strategies to achieve change is to mainstream biodiversity into sectoral policies. Mainstreaming, a concept that can be traced back to the Brundtland report, promotes the integration of the environment into political, societal, and economic planning and decision-making. Based on the review of key studies undertaken during the regional assessment for Europe and Central Asia, we develop a stepwise approach to analyze the current status of mainstreaming of biodiversity and NCP. The approach can be used both for policy design purposes and diagnostic evaluations. It demonstrates that mainstreaming has the potential to improve the conservation and sustainable use of biodiversity as well as the sustained provision of NCP. However, based on the status of implementation across Europe and Central Asia, we conclude that mainstreaming needs to be pursued and implemented in a stronger and more systematic way. The results of our assessment provide important input to national strategies and policies but also to the ongoing process of the Conference of the Parties to the Convention on Biological Diversity while developing the post-2020 global biodiversity framework.